Aplikasi Reservasi Kamar Berbasis Web: Solusi untuk Meningkatkan Pemesanan di Wisma Rumka - Putri, Kezia Agatha; Wasito, Budi (Jurnal Informatika dan Bisnis, 2024)
Wisma Rumka is a place that operates in the accommodation sector. Wisma Rumka provides accommodation in the form of accommodation for one night or one month. Wisma Rumka consists of 21 rooms dan has a 4-story building. The research carried out aims to increase goal is to reduce synchronization between room scheduling and the reservation process. The theories used in this research are theories about system, reservations, 8 golden rules, and other theories that can support this research. System theory is used as the foundation for creating a reservation system, reservation theory as a variable in the system being created, along with the 8 golden rules as a theory to make the appearance better. The research method used is qualitative research method. The primary data needed in this research was obtained from sctructured interviews with the owner of Wisma Rumka and the result of field research at the accommodation. The secondary data needed in this research was obtained from the author reading books and journals. The website design is depicted with a UML diagram. The resulting website is a website in the form of a simple reservation that can be opened via computer and the display has been adapted to mobile display. This website is used to support room booking activities carried out by Wisma Rumka Inn. This research was carried out the aim of creating a reservation website using PHP, HTML, MySQL so that it does not required any costs. It is hoped that this research can be one of the things that can increase room bookings.